Expressive Language and the Impact of Zinc/Copper Ratio - Strauss, Gabrielle (My University, 2018)
The interaction between genes and the environment such as mineral and trace elements are now regarded as the most probable explanation of autism (Yasuda, Yoshida, Yasuda, & Tsutsui, 2013). Weismer, Lord, and Esler (2010) identified children associated with pervasive developmental disorder not otherwise specified (PDD-NOS) and autism have exhibited substantial language delays compared to children of their chronological age. Language delays were found to profoundly impact both receptive and expressive language. The participant in this study was a three year-old female who was previously diagnosed with Autism Spectrum Disorder (ASD). For the experiment, the child was administered articulation and language standard evaluations in order to create expressive language goals. The participant’s clinician created language goals and skilled speech therapy initiated. The participant was administered a 50mg zinc supplement nine weeks into therapy to measure the effects of this trace element on expressive language. The results were inconclusive in that the participant exhibited improved language abilities with and without zinc. Continuous research is warranted to gain better understanding of the effects of zinc supplementation on expressive language in children associated with ASD.
Introduction 1 Review Of The Literature 5 Pervasive Developmental Disorders 5 Role Of Zinc 7 Zinc Supplementation Related To Treatment 11 Language Deficits 11 Methods 15 Participants 15 Procedures 15 Initial Speech And Language Evaluation 15 Measurement Of Zinc And Copper Levels 16 Administration Of Zinc Supplement 17 Collection Of Data During Therapy 18 Analysis 19 Results 20 Summary Of Expressive Language Function Without Zinc Supplementation 20 Heavy Metal Test Results 21 Discussion 27 Limitations And Recommendations 29 Conclusions 30 References 31 Appendix A 35 Appendix B 39
Keywords: Zinc; Copper; Autism